Analisis Pengaruh Tingkat Pengangguran Terbuka, IPM, dan PDRB terhadap Kemiskinan di Kabupaten/Kota Provinsi Bali Tahun 2018-2022 - Noviyanti, Ni Komang; Savitri, Kadek Shri Yogi (Jurnal Bali Membangun Bali, 2023)
Purpose: This paper aims to determine the effect of the open response rate, Human Development Index, and GRDP on poverty in the level II regions of Bali Province in 2018-2022. Research methods: The research consists of four variables consisting of one dependent variable and three independent variables. The data used are secondary data from the Central Bureau of Statistics and journals. The data processed is quantitative data from 2018-2022 used SPSS ver. 25. Results and discussions: 84.20% of poverty is influenced by the open unemployment rate, human development index, and GRDP, while 15.80% is influenced by other variables. Unemployment rate has a positive effect on poverty, human development index has a negative effect on poverty, and GRDP has a positive effect on poverty. Implication: This research is limited to independent variables such as the Human Development Index, Open Unemployment Rate, and GRDP. Therefore, the development of this research can still be carried out by including other variables that do not exist in this study. In addition, future researchers can also expand the object of research in the form of regions in Indonesia and use other methods to see the effect of the variables studied.